Racial superiority arguments in Grant's PASSING OF THE GREAT RACE and Higham's STRANGERS IN THE LAND - Krampera, Michal (Univerzita Pardubice, 2016)
The bachelor paper deals with racial ideologies and the idea of racial superiority in the first half of the 20th century in the United States. Individual theories from Madison Grant’s The Passing of the Great Race and John Higham’s Strangers in the Land are compared and analyzed in context with American immigration policy and the authors’ background.
Keywords: nativism; racial superiority; racism; new immigration; eugenics; Nordic race; nativismus; rasová nadřazenost; rasismus; noví imigranti; eugenika; nordická rasa